MEMBEDAH NILAI PERUSAHAAN: PERAN STRATEGIS KINERJA LINGKUNGAN, KEUANGAN, INVESTASI, PENDANAAN, DAN SKALA USAHA : DISSECTING CORPORATE VALUE: THE STRATEGIC ROLE OF ENVIRONMENTAL PERFORMANCE, FINANCE, INVESTMENT, FUNDING, AND BUSINESS SCALE - Canggih, Canggih; Efni, Yulia; Fiona, Fiona (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This research aims to investigate the impact of financial performance, investment decisions, financing decisions, and firm size on company value. The study focused on companies in the property and real estate sectors listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. Secondary data were obtained from the companies' annual reports and analyzed using a quantitative approach. The research employed purposive sampling, resulting in a final sample of forty-five companies. Data analysis was performed using multiple linear regression analysis. The findings indicated that firm value was not influenced by environmental performance, was positively and significantly affected by financial performance, was not affected by investment decisions, was positively and significantly impacted by funding decisions, and was not influenced by firm size